2016
DOI: 10.1186/s12960-016-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the specialty choice of Korean medical students: a cross-sectional survey

Abstract: BackgroundAn imbalance of physician supply by medical specialty has been observed in most countries. In Korea, there is a greater tendency to avoid surgical specialties and specialty choices in nonclinical medicine, such as the basic science of medicine. In this study, we identified factors affecting the specialty choice of physicians in order to provide a basis for policies to address this problem.MethodsWe used the results of a 2013 nationwide survey of 12 709 medical students (82.7 % responded) to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Because of the population ageing, increased workload on doctors through increased number of consultations and in managing patients with multimorbidity, the demand for physicians continues to increase; however, an imbalance in the supply of physicians in different subspecialties has become a growing concern in both developed and developing countries 1–5. Some specialties and subspecialties, such as family medicine and palliative medicine,6 7 are experiencing a desperate shortage of physicians, whereas other specialties and subspecialties, such as cardiology, ophthalmology and ear, nose and throat surgery, are highly competitive specialties with low success rate for candidates 8 9…”
Section: Introductionmentioning
confidence: 99%
“…Because of the population ageing, increased workload on doctors through increased number of consultations and in managing patients with multimorbidity, the demand for physicians continues to increase; however, an imbalance in the supply of physicians in different subspecialties has become a growing concern in both developed and developing countries 1–5. Some specialties and subspecialties, such as family medicine and palliative medicine,6 7 are experiencing a desperate shortage of physicians, whereas other specialties and subspecialties, such as cardiology, ophthalmology and ear, nose and throat surgery, are highly competitive specialties with low success rate for candidates 8 9…”
Section: Introductionmentioning
confidence: 99%
“…It is in accordance with previous studies regarding medical students' career preferences both domestically and internationally. [1][2][3][4][11][12][13][14][15] The second most chosen career as the first choice was as a general practitioner. The result was similar to the previous study shown that GP is still considered as career preference.…”
Section: Discussionmentioning
confidence: 99%
“…Most of medical students choose specialty as their preferred medical career. [1][2][3] Many factors influence the career specialty decisions made by medical students. [3][4][5][6] These factors embrace a wide spectrum of influences and range from traditional motivators such as individual characteristics or anticipation of specialty-related income, to generation Y's typical career preferences, such as personal time free from practice requirements for leisure, family and vocational pursuits, along with control of the total number of hours per week spent on fulfilling professional responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Besides economic motifs, multiple drivers are believed to be at the heart of medical students' choice of specialties. Evidence exists linking preference for specific specialties to medical students' socio-economic characteristics [9], to their valuation of future job opportunities [10], and to the characteristics of the training received [11]. Labour market forces and prospective revenues have also been identified as major influencing factors in the selection of specialties, with the expected Rate of Return to Education for specific medical professions being a key, and still largely unexplored, determinant of students' decisions [12].…”
Section: Introductionmentioning
confidence: 99%